PENGARUH KONSENTRASI GIBERELIN (GA3) DENGAN WAKTU APLIKASI SEBELUM PANEN TERHADAP MUTU FISIK TANDAN BUAH SEGAR KELAPA SAWIT (Elaeis guineensis Jacq.) - Sri Murti Tarigan; Eka Bobby Febrianto; Lufy Andria Cik (Institut Teknologi Sawit Indonesia (ITSI), 2019)
Physical damage to fruit on oil palm fresh fruit bunches due to harvest and postharvest activities include injuredfruit mesocarp, fruit weight loss, and loss in fruit bunches. One of the postharvest handling that can maintainthe physical quality of the fruit is by giving gibberellins (GA3). This research aims to determine the effect of theconcentration of gibberellins (GA3) whit application time before harvest on the physical quality of postharvestoil palm fresh fruit bunches. The research was conducted at Afdeling VI Garden Cot Girek PT. PerkebunanNusantara I and in the Cot Girek Palm Oil Factory laboratory. The time of the research was conducted in Juneuntil July 2019. The study used a non factorial randomized block design method with 4 treatment levels (0 mg/l,50 mg/l, 100 mg/l, and 150 mg/l) with 3 replications. The administration of gibberellins has a significant effecton fruit loss and fruit weight reduction with the best concentration og gibberellins is 50 ppm but does not havea significant efffect on pH, moisture content, and fruit free fatty acids.